Islamic Education Research, 2000–2025: Publication Dynamics, Core Topics, and Global Collaboration Patterns - Judijanto, Loso (West Science Islamic Studies, 2026)
This paper analyzes the evolution of literature in the area of Islamic Education from 2000 to 2025 using bibliometric methods. Analyzing data from Scopus and applying the VOSviewer software program, publication trends, intellectual structure, and international cooperation in this sphere have been identified. The results show an impressive growth of publications and dominance of Southeast Asian countries (Indonesia and Malaysia). As for the collaboration pattern, the research found the presence of moderately well-connected networks limited by geographical proximity. Analysis of citations proves the interdisciplinary character of important papers, as they relate to both education and such fields as social science, psychology, and culture. Finally, keyword co-citation and keyword overlay analysis prove that a transition from purely religious concepts to more practical ones takes place: there is a growing interest in issues related to curricula, e-learning, and religious moderation.